Statistical study of Doppler velocity and echo power around 75゜ magnetic latitude using data obtained with the Syowa East HF radar in 1997 - Fukumoto, Masaaki; Nishitani, Nozomu; Ogawa, Tadahiko; Sato, Natsuo; Yamagishi, Hisao; Yukimatu, Akira Sessai (National Institute of Polar Research, 2000)
P(論文) We present the statistical relationship between the echo power and Doppler velocity of radar echoes observed with the Syowa East HF radar in Antarctica in 1997. The objective of this analysis was to clarify the mechanisms by which high-latitude (～75° magnetic latitude) F region irregularities are generated. Although data points are scattered over a large area, a positive correlation between Doppler velocity and echo power appears to be present. This relationship can be interpreted in terms of gradient-drift instability, which is the most probable cause of the decameter-scale irregularities in the F region. The positive correlation deteriorates in the afternoon and midnight sectors, probably as a result of other mechanisms related to particle precipitation (field-aligned current), such as the current-convective instability. departmental bulletin paper